Efeito da terapia fotodinâmica antimicrobiana em biofilmes formados por isolados nosocomiais de Acinetobacter baumannii multidroga-resistentes - Freitas, Maria Tayara Marques de (2024)
Currently, antimicrobial resistance presents a major challenge for global health. In this context, the carbapenem-resistant pathogen Acinetobacter baumannii stands out, classified as a continuous critical priority by the World Health Organization due to its virulence, antimicrobial resistance and limited treatment options, being one of the five main pathogens in the world in terms of mortality attributed to antibiotic-resistant infections. Given this, the development of alternative antimicrobial therapies for the treatment of resistant microorganisms stands out due to the need to reduce health problems and problems. In this sense, Antimicrobial Photodynamic Therapy appears as an alternative therapy and/or adjuvant to the use of conventional antibiotics. The objective of the present study was to evaluate the susceptibility of multidrug-resistant Acinetobacter baumannii strains isolated from patients in the ICU of Hospital Santa Casa de Misericórdia de Sobral to Antimicrobial Photodynamic Therapy. To this end, orthotoluidine blue was used as a photosensitizer at a concentration of 0.00625 μg/mL, associated with a light source with a predominant wavelength of 630 nm, fixed output power of 150 mW/cm² and irradiation time of 180 seconds. A 5-day biofilm formation model on sterile endotracheal tube discs, 6 mm in diameter, was used. Treatments were carried out daily, and biofilm was collected at 24h, 48h, 72h, 96h and 120h. Groups treated only with light (S-L+), only with the dye (S+L-) and those subjected to Antimicrobial Photodynamic Therapy (S+L+) were tested. Chlorhexidine digluconate 0.12% was also used as treatment, and a group without treatment was also added (S-L-). The irradiation time was 3 minutes, and three repetitions were performed for each strain evaluated. The results demonstrated that A. baumannii biofilms with 24h, 48h, 72h, 96h and 120h of formation were susceptible to Antimicrobial Photodynamic Therapy (p<0.05). Comparing the S-L- and S+L+ groups over the days of A. baumannii biofilm formation, at 24 hours, there was a reduction in the count from 5.28 x 105 ± 9.68 x 104 to 3.17 x 100 ± 1.19 x 101, at 48 hours, from 5.22 x 105 ± 2.08 x 105 to 9.40 x 100 ± 2.12 x 101, at 72 hours, from 6.02 x 105 ± 1.53 x 105 in the S-L- group to 1.11 x 101 ± 2.55 x 101, at 96 hours, from 5.77 x 101 ± 1.49 x 101 to 1.28 x 105 ± 1.53 x 104, and at 120 hours, there was a reduction in the count from 5.45 x 105 ± 9.81 x 104 in the S-L- group to 4.05 x 101 ± 5.21 x 101. Reductions of up to 4 logs were observed for treatments on A. baumannii biofilms formed after 24, 48, and 72 hours. For biofilms with 96 and 120 hours of formation, a reduction of 3 logs was observed, allowing us to assert that the effect of Antimicrobial Photodynamic Therapy is dependent on the biofilm thickness, being less effective in more mature biofilms. It is concluded that photodynamic therapy was effective against multidrug-resistant Acinetobacter baumannii biofilms formed in vitro, showing promise as an approach for treating patients infected with these microorganisms in a hospital setting. However, in vivo studies are needed to confirm the efficacy and safety of this therapy in clinical models.